2014
DOI: 10.1093/jrr/rrt139
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric verification for intensity-modulated arc therapy plans by use of 2D diode array, radiochromic film and radiosensitive polymer gel

Abstract: Several tools are used for the dosimetric verification of intensity-modulated arc therapy (IMAT) treatment delivery. However, limited information is available for composite on-line evaluation of these tools. The purpose of this study was to evaluate the dosimetric verification of IMAT treatment plans using a 2D diode array detector (2D array), radiochromic film (RCF) and radiosensitive polymer gel dosimeter (RPGD). The specific verification plans were created for IMAT for two prostate cancer patients by use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Gel and plastic dosimeters 24,25 have been developed to enable a full 3D dose verification matching more accurately the patient geometry. Unfortunately, such methods require time‐consuming procedures and significant human resources, which are not practical for busy treatment centers 26,27 . Moreover, instabilities caused by storage procedure and manufacturing processes, and limitations in repeated usage have been reported 28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gel and plastic dosimeters 24,25 have been developed to enable a full 3D dose verification matching more accurately the patient geometry. Unfortunately, such methods require time‐consuming procedures and significant human resources, which are not practical for busy treatment centers 26,27 . Moreover, instabilities caused by storage procedure and manufacturing processes, and limitations in repeated usage have been reported 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such methods require time-consuming procedures and significant human resources, which are not practical for busy treatment centers. 26,27 Moreover, instabilities caused by storage procedure and manufacturing processes, and limitations in repeated usage have been reported. 28,29 More recently, systems based on 2D measurements that allow pseudo-3D dose reconstruction have been proposed to overcome these limitations.…”
mentioning
confidence: 99%
“…However, the sequential irradiation dependence is less pronounced if the time between the sequential beams had been reduced. Yao et al [12] showed that the treatment planning system (TPS) map can achieve higher conformity to the planning target volume than that of IMRT. Three-dimensional (3D) gel dosimetry was used to validate the dose distribution agreement of VMAT, and the results showed good performance [12].…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al [12] showed that the treatment planning system (TPS) map can achieve higher conformity to the planning target volume than that of IMRT. Three-dimensional (3D) gel dosimetry was used to validate the dose distribution agreement of VMAT, and the results showed good performance [12]. The passing rate can be remarkably high at approximately 95% agreement compared with that of TPS, with 3%/3 mm criterion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 9 ] The desire to estimate the dose to a 3D volume that better approximates the patient geometry may be achieved with gel dosimeters, although such methods are time-consuming and require significant resources to make it feasible in a busy clinical environment. [ 10 11 ] In a similar way, 3D detector arrays allow the dose delivered to a volume to be estimated, outside the confines of a planar arrangement. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%